KAJIAN PUSTAKA BEBERAPA TANAMAN INDONESIA DENGAN AKTIVITAS ANTIHIPERTENSI DAN STUDI INTERAKSI ZAT BERPOTENSI ANTIHIPERTENSI TERHADAP RESEPTOR ANGIOTENSIN CONVERTING ENZYME SECARA IN SILICO - Adinindya Putri, Raras
Hypertension cases are always increasing every year in Indonesia. This may be caused by the relatively low awareness, therapy, and control of hypertension in the community. It can be concluded that hypertension treatment methods needs to be developed continuously. One way to do that is to analyze resources with potential antihypertensive activity in Indonesia. This literature review contains several Indonesian plants that are clinically and preclinically proven to have antihypertensive activity. An in silico experiment on the interaction of potential antihypertensive compounds from various plants was also carried out against Angiotensin Converting Enzyme (ACE) receptor to determine the interactions that occur so that they can be investigated further. The target receptor used was human testicular angiotensin I-converting enzyme (PDB ID: 1UZF). The natural ligand used is MCO (1-(3-mercapto-2- methyl-propionyl)-pyrolidine-2-carboxylic acid) or better known as captopril. Compounds tested are the main component of Indonesian plants with antihypertensive potential that have not been tested clinically or preclinically, namely buni (Antidesma bunius Spreng), trengguli (Cassia fistula Linn), lubilubi (Flacourtia inermis Roxb.), ranti (Solanum nigrum Linn), pulai (Alstonia spectabilis R. Br), and srigading (Nyctanthes arbor-tristis L.). The three-dimensional structure of the test compounds were optimized using GaussView 6.0.16 and Gaussian 09W. In silico molecular docking studies were carried out with the Autodock 4.2.3 program. Docking results were analyzed using Notepad++ and BIOVIA Discovery Studio Visualizer. Based on the in silico analysis, the compounds predicted to have antihypertensive potential against the ACE receptor were catechins from buni and solasodine from ranti.